Diseño contemporáneo de una plaza comercial en la ciudad de Babahoyo - Aguilar Sánchez, Geanella Solange (2023)
The thesis focuses on the contemporary design of a commercial plaza for the city of Babahoyo, Ecuador. The city is undergoing high growth towards the periphery areas due to the lack of spaces for housing construction within it. This has given way to construction companies focusing on developing urban projects and therefore an increase in the resident population. Currently, the city lacks commercial buildings in the area and access to the city center is becoming more complicated every day. Therefore, the thesis proposal is to plan pleasant spaces and landscapes for a commercial plaza that responds to the lack of commercial buildings in the area and improves accessibility to the city. The importance of the shopping plaza lies in the fact that it will not only be of benefit to the users of the environment, but it will also contribute to tourism and the architectural development of the city. The thesis consists of four chapters. The problem that determines the investigation is raised in chapter one. The challenges, inconveniences or deficiencies that are intended to be undertaken through the thesis are recognized and explained. In addition, the interest of resolving this issue in the context of architecture is established. The theoretical and legal framework that supports the investigation is presented as a second chapter. Existing literature, theories and relevant ideas are verified to encompass and analyze the subject of study. In addition, the rules, laws and regulations are investigated. The third chapter describes the methodology used for the research. It explains how the research was carried out and details the methods used to collect and analyze the data. Finally, the fourth chapter presents the results of the investigation and the design proposal of the commercial plaza. The design elements are described and the corresponding plans and models are presented. In conclusion, the thesis proposes an architectural solution for the lack of commercial buildings in the city of Babahoyo, improving accessibility and contributing to the development of the city.